The Nature and Types of Organizational Taxonomies: An Overview - Carper, William B.; Snizek, William E. (Academy of Management Review, 1980)
Although organizational taxonomies have been the subject of numerous conceptualizations and several research studies, no generally accepted method of classifying organizations has yet been formulated. This article provides a critical review of these past theoretical and empirical efforts in an attempt to establish a research foundation for future investigations.